Information Technologies in Industrial Enterprises Production Assets Management - Kovin R. V. Roman Vladimirovich; Kudinov A. V. Anton Viktorovich; Markov N. G. Nikolai Grigorevich; Miroshnichenko E. A. Evgeny Alexandrovich (Information Technology, Data and Signal Processing, 2016)
Title screen